Rapid Detection of Enterocytozoon hepatopenaei Infection in Shrimp With a Real-Time Isothermal Recombinase Polymerase Amplification Assay - Ma, Chao; Fan, Shihui; Wang, Yu; Yang, Haitao; Qiao, Yi; Jiang, Ge; Lyu, Mingsheng; Dong, Jingquan; Shen, Hui; Gao, Song (Frontiers in Cellular and Infection Microbiology, 2021)
Enterocytozoon hepatopenaei (EHP) infection has become a significant threat in shrimp farming industry in recent years, causing major economic losses in Asian countries. As there are a lack of effective therapeutics, prevention of the infection with rapid and reliable pathogen detection methods is fundamental. Molecular detection methods based on polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP) have been developed, but improvements on detection speed and convenience are still in demand. The isothermal recombinase polymerase amplification (RPA) assay derived from the recombination-dependent DNA replication (RDR) mechanism of bacteriophage T4 is promising, but the previously developed RPA assay for EHP detection read the signal by gel electrophoresis, which restricted this application to laboratory conditions and hampered the sensitivity. The present study combined fluorescence analysis with the RPA system and developed a real-time RPA assay for the detection of EHP. The detection procedure was completed in 3–7 min at 39°C and showed good specificity. The sensitivity of 13 gene copies per reaction was comparable to the current PCR- and LAMP-based methods, and was much improved than the RPA assay analyzed by gel electrophoresis. For real clinical samples, detection results of the real-time RPA assay were 100% consistent with the industrial standard nested PCR assay. Because of the rapid detection speed and the simple procedure, the real-time RPA assay developed in this study can be easily assembled as an efficient and reliable on-site detection tool to help control EHP infection in shrimp farms.